Effect of Cytotoxic T-Lymphocyte Antigen-4 on the Efficacy of the Fatty Acid-Binding Protein Vaccine Against Schistosoma japonicum - Tang, Chun-lian; Pan, Qun; Xie, Ya-ping; Xiong, Ying; Zhang, Rong-hui; Huang, Jin (Frontiers in Immunology, 2019)
The present study evaluated the impact of blocking cytotoxic T-lymphocyte antigen-4 (CTLA-4) activity on the protective effect elicited by the fatty acid binding protein (FABP) vaccine against Schistosoma japonicum infection. Mice were randomly divided into uninfected, infected control, anti-CTLA-4 monoclonal antibody (anti-CTLA-4 mAb), FABP, and combination (anti-CTLA-4 mAb and FABP) groups. An assessment of the S. japonicum worm and egg burden in the infected mice revealed that the worm reduction-rate induced by FABP administration was increased from 26.58% to 54.61% by co-administration of the monoclonal anti-CTLA antibody (anti-CTLA-4 mAb). Furthermore, the regulatory T cell (Treg) percentage was significantly increased in mice after administration of the anti-CTLA-4 mAb, but not the FABP vaccine, and elevated levels of the cytokines interferon (IFN)-γ, interleukin (IL)-2, IL-4, and IL-5 were observed in infected mice that were administered the anti-CTLA-4 mAb. Notably, the diameter of egg granulomas in the anti-CTLA-4 mAb and combination groups was significantly increased compared to that observed in the infected control group. Together, these results suggest that co-administering the FABP vaccine and anti-CTLA-4 treatment may have synergistically increased the immunoprotective effect of the FABP vaccine by promoting T-helper 1-type immune responses, while incurring increased tissue damage.